Quality of Life and Unmet Need in People with Psychosis in the London Borough of Haringey, UK. (19th November 2012) - Lambri, Maria; Chakraborty, Apu; Leavey, Gerard; King, Michael
Abstract : Objectives . Deinstitutionalization of long-term psychiatric patients produced various community-based residential care facilities. However, inner-city areas have many patients with severe mental illness (SMI) as well as deprivation, unemployment, and crime. This makes meeting their community needs complex. We undertook a needs assessment of service provision and consonance between service users' evaluation of need and by care workers. Design . Cross-sectional study with random sample of SMI service users in four housing settings: rehabilitation units; high-supported; medium-supported; low-supported housing. Setting . London Borough of Haringey. Outcome Measures . 110 SMI service users and 110 keyworkers were interviewed, using Camberwell Assessment of Need; SF-36; Lancashire Quality-of-Life profile; demographic and clinical information. Results . People in "low-support" and "high-support" housing had similar symptom scores, though low support had significantly lower quality of life. Quality of life was positively predicted by self-reported mental-health score and negatively predicted by unmet-need score in whole sample and in medium-support residents. Residents' and care-workers' assessments of need differed considerably. Conclusions . Although patients' housing needs were broadly met, those in low-supported housing fared least well. Attendance to self-reported mental health and unmet social needs to quality of life underpins planning of residential services for those with SMI. Social and personal needs of people in supported housing may be underestimated and overlooked; service providers need to prioritise these if concept of "recovery" is to advance.